2019
DOI: 10.1089/photob.2018.4615
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of 660 and 830 nm Photobiomodulation in Promoting Orthodontic Tooth Movement

Abstract: Objective: Photobiomodulation (PBM) can usefully promote wound healing and relieve pain via its biological effects, with a wide range of applications in clinical medicine. The aim of the present study was to investigate the effect of 660 and 830 nm PBM on orthodontic tooth movement. Background data: PBM is based on the biological effects of diode laser irradiation on tissues, promoting cell proliferation and activity. Materials and methods: An orthodontic force was applied to the upper right first molars expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The ETM was measured to assess another effect of laser irradiation. Recently, a significant increase in tooth movement mediated by irradiation with 660 or 830 nm lasers was reported (47). Laser irradiation also significantly increased the expression of interleukin-1β (IL-1β), receptor activator of nuclear factor κ-B ligand (RANKL), and osteoprotegerin (OPG) and the activity of osteoclasts in a wavelength-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The ETM was measured to assess another effect of laser irradiation. Recently, a significant increase in tooth movement mediated by irradiation with 660 or 830 nm lasers was reported (47). Laser irradiation also significantly increased the expression of interleukin-1β (IL-1β), receptor activator of nuclear factor κ-B ligand (RANKL), and osteoprotegerin (OPG) and the activity of osteoclasts in a wavelength-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The increased demand for rapid orthodontic treatment has led to the introduction of several methods, which also reduce potential risks of dental and periodontal complications such as external apical root resorption, high levels of dental caries, and subsequent gingivitis and periodontitis [3][4][5]. Some of the proposed methods are adequate use of brackets, controlling force levels, and relying on less friction bracket systems, photobiomodulation, pharmacological approaches, or low-intensity laser irradiation [6][7][8][9][10][11]. However, irrespective of the method, the rate of the tooth movement is dictated by the biologic response to the applied orthodontic forces [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, wavelengths between 700 nm and 850 nm deeply penetrate the tissues, with two peaks around 725 nm and 810 nm [ 46 ]. Other studies have shown that the wavelengths that deliver concrete orthodontic effects are 630 nm, 660 nm, 830 nm, and 850 nm [ 47 , 48 ]. The wavelength of the light, the thickness of the target tissue, and the degree of the keratinization and pigmentation of the oral mucosa may all have an impact on the depth of penetration.…”
Section: Discussionmentioning
confidence: 99%